Development of an interactive computer program for advance care planning. - Green MJ; Levi BH (Health Expectations, 2009)
OBJECTIVE: To describe the development of an innovative, multi-media decision aid for advance care planning. BACKGROUND: Advance care planning is an important way for people to articulate their wishes for medical care when they are not able to speak for themselves. Living wills and other types of advance directives are the most commonly used tools for advance care planning, but have been criticized for being vague, difficult to interpret, and inconsistent with individuals' core beliefs and values. RESULTS: We developed a multimedia, computer-based decision aid for advance care planning ('Making Your Wishes Known: Planning Your Medical Future') to overcome many of the limitations of standard advance directive forms. This computer program guides individuals through the process of advance care planning, and unlike standard advance directives, provides tailored education, values clarification exercises, and a decision-making tool that translates an individual's values and preferences into a specific medical plan that can be implemented by a health-care team. Pilot testing with 50 adult volunteers recruited from an outpatient primary care clinic showed high levels of satisfaction with the program. Further pilot testing with 34 cancer patients indicated that the program was perceived to be highly accurate at representing patients' wishes. CONCLUSIONS: This paper describes the development of an innovative decision aid for advance care planning that was designed to overcome common problems with standard advance directives. Preliminary testing suggests that it is acceptable to users and is accurate.